LEARNING AND RESEARCHING THE CULTURAL ENVIRONMENT OF THE LANGUAGE BY USING COLOR RELATED WORDS - Umarqulova, Maxliyo (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This article delves into the intricate relationship between language and culture through the lens of color-related words. It provides an in-depth exploration of how different cultures perceive and articulate colors, uncovering the rich tapestry of meanings, associations, and symbolism embedded within linguistic expressions of color. Drawing on interdisciplinary research from linguistics, anthropology, psychology, and semiotics, the author examines how cultural norms, historical contexts, and societal factors influence the use and interpretation of color-related language. Through a systematic review of linguistic data and cultural artifacts, the article elucidates the diverse ways in which colors are conceptualized and employed across various linguistic communities. It sheds light on the cultural significance attached to specific colors, uncovering underlying narratives, beliefs, and rituals that shape color perception and usage. Furthermore, the article analyzes cross-cultural differences and similarities in color categorization, highlighting the role of language as a reflection of cultural values and worldview.